Problemas jurisdiccionales entre agustinos y dominicos en las misiones del norte de Luzón (Filipinas) en la primera mitad del siglo XVIII (Estudios humanísticos. Geografía, historia y arte, 1994)
This paper studies the problems and confrontations between Augustinians and Dominicans in Northern Luzon at the beginning of the XVIIIth century. The origin of these troubles was the lack of jurisdictional and administrative limits that would clearly divide the provinces of Pangasinan and Pampanga. The Dominicans were in charge of the christianization of Pangasinan, and the Augustians, of the province of Pampanga. After 23 years of conflict, the Augustinians generously handed over to the Dominicans the missions they had founded in the mountain-region of Ituy and Buhay.